Economic Dependency and Ecological Challenges in Artisanal Gold Mining: A Case Study of Local Wisdom in Tedeboe Village - Yesaya Kaho; Feliks Arfid Guampe; Olvit Olniwati Kayupa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study explores the dual impact of artisanal gold mining on economic livelihood and environmental sustainability in Tedeboe Village, Rampi District, North Luwu Regency. Employing a qualitative case study design, data were gathered through in-depth interviews with four key informants—including the village head and three local miners—and through direct field observation. Data were analyzed using Creswell’s qualitative analysis framework, encompassing coding and thematic development to capture nuanced insights. The findings indicate that artisanal gold mining has significantly improved household income, especially in meeting basic needs and funding education. However, the sector’s informal nature and high dependency expose the community to economic volatility. Moreover, despite limited use of chemicals, awareness of mercury’s environmental and health risks is rising among miners. Environmental degradation, particularly soil and water pollution, alongside potential respiratory hazards, emerges as a critical concern. The study underscores the urgent need for sustainable mining practices, stronger local regulation, and capacity-building through education and economic diversification. These findings advocate for a balanced approach to rural development—one that harmonizes economic benefits with ecological resilience and community well-being.